Փոքր և միջին ձեռնարկությունների գործունեության խթանման հիմնախնդիրները Հայաստանի Հանրապետությունում - Արմինե Գրիգորիի Զախարյան (ՀՀ ԳԱԱ հրատ.)
Настоящая статья посвящена проблеме стимулирования деятельности малых и средних предприятий в Республике Армения. Учитывая влияние сферы МСП на развитие экономики РА, в статье сделана попытка выявления возможностей дальнейшего улучшения экономического положения РА посредством стимулирования деятельности малых и средних предприятий. This article discusses the issues on stimulating the activity of small and medium-sized enterprises (SMEs) in the Republic of Armenia. By taking into account the impact of the SME sector on the development of the economy in the Republic of Armenia, the article attempts to identify opportunities to further improve the economic situation in the Republic of Armenia by stimulating the activity of small and medium-sized enterprises.
Keywords: Հասարակական գիտություններ; Տնտեսագիտություն; Ֆինանսներ